AGRICULTURE RESOURCE AND ECONOMIC GROWTH IN NIGERIA - Olajide, O. T.; Akinlabi, B. H.; Tijani, A. A. (European Scientific Journal, ESJ, 2012)
The paper analyses the relationship between Agricultural resource and economic growth in Nigeria. The Ordinary Least Square regression method was used to analyze the data. The results revealed a positive cause and effect relationship between gross domestic product (GDP) and agricultural output in Nigeria. Agricultural sector is estimated to contribute 34.4 percent variation in gross domestic product (GDP) between 1970 and 2010 in Nigeria. The Agricultural sector suffered neglect during the hey-days of the oil boom in the 1970s. In order to improve agriculture, government should see that special incentives are given to farmers, provide adequate funding, and also provide infrastructural facilities such as good roads, pipe borne water and electricity.